PATHOGENETIC MECHANISMS OF LEPTIN RESISTANCE - G. A. Chumakova; A. V. Ott; N. G. Veselovskaya; O. V. Gritsenko; N. N. Shenkova (Российский кардиологический журнал)
Leptin is a regulatory protein from adipokines family, that maintain energy homeostasis of the body and deter obesity development. Impaired transfer of leptin signals to hypothalamus leads to leptin resistance and its adverse complications. Understanding of leptin resistance mechanisms is pivotal for the development of preventive and treatment procedures aiming to decrease the risk of atherosclerosis,